REDUPLIKASI DALAM ACARA HITAM PUTIH DI STASIUN TELEVISI TRANS 7 - Nora Asmaya; Hasnah Faizah AR; Charlina ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research discusses reduplication in realitity show Hitam Putih on Television Stasion Trans 7. The objectives of this research are (1) to describe the from of reduplication in talkshow Hitam Putih on Television Stasion Trans 7, (2) to describe the meaning of reduplication in talkshow Hitam Putih on Television Station Trans 7. The method used is a qualitative method that describes the descriptive data. In this study, the quthor used three data collection techniques first, downloading talkshow Hitam Putih impression video that aired on Television Station Trans 7. Second, obeserving the reduplication used in talkshow Hitam Putih impressions used in talkshow Hitam Putih impressions on Television Station Trans 7. Third, copy all reduplication present in talkshow Hitam Putih impressions on Television Station Trans 7. The source of this research data is the whole show talkshow Hitam Putih on Television Station Trans 7.Keywords: Reduplication, Hitam Putih.